2018
DOI: 10.1063/1.5051638
|View full text |Cite
|
Sign up to set email alerts
|

Electromigration in gold nanowires under AC driving

Abstract: We investigate the relationship between temperature and electron wind force in electromigration (EM) of ultrathin gold nanowires by monitoring power and current density at breakdown under a generalized AC bias (AC with a DC offset). Based on model calculations, our driving frequency of 10 MHz is low enough to maintain steady state self-heating behavior of our wires but high enough that the direction of the wind force switches quickly relative to the time-scale of atomic motion through the junction. The maximum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The nanogap with single nanometer scale in width can be reproducibly formed. When we apply iFBEM, because iFBEM has no fixed polarity direction, the nanogap forms near the center between the cathode and anode electrodes . The iFBEM can also reproduce the gap size if the applied voltage and the measurable current are adjusted to the same parameter .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The nanogap with single nanometer scale in width can be reproducibly formed. When we apply iFBEM, because iFBEM has no fixed polarity direction, the nanogap forms near the center between the cathode and anode electrodes . The iFBEM can also reproduce the gap size if the applied voltage and the measurable current are adjusted to the same parameter .…”
Section: Resultsmentioning
confidence: 99%
“…This indicates that the reconstruction of the Au electrodes was conducted for the four images and suggests that inversing the bias voltage application encourages the Au reconstruction. The Au reconstructions in a vacuum using several application of inversing bias voltages have already been reported . The reconstructed Au nanogap electrodes were automatically achieved by using the iFBEM.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[26] The results of previous investigations into the lifetimes of various electronic devices have revealed that the application of an alternating current (AC) or a pulsed current to a material can produce a damage-recovery effect by inducing mechanical stress relaxation during the off-time of the duty cycle. [27][28][29][30][31] These studies focused on preventing electromigration or thermal damage. However, thus far, no reports exist on theoretical or experimental investigations into how manipulation of the atomic arrangement can be realized and how it can improve the material properties.…”
Section: Introductionmentioning
confidence: 99%